Effect of exclusive breastfeeding on selected adverse health and nutritional outcomes: a nationally representative study - Md. Nuruzzaman Khan; M. Mofizul Islam (BMC, 2017)
Abstract Background Despite growing evidence in support of exclusive breastfeeding (EBF) among infants in the first 6 months of birth, the debate over the optimal duration of EBF continues. This study examines the effect of termination of EBF during the first 2, 4 and 6 months of birth on a set of adverse health and nutritional outcomes of infants. Methods Three waves of Bangladesh Demographic and Health Survey data were analysed using multivariate regression. The adverse health outcomes were: an episode of diarrhea, fever or acute respiratory infection (ARI) during the 2 weeks prior to the survey. Nutritional outcomes were assessed by stunting (height-for-age), wasting (weight-for-height) and underweight (weight-for-age). Population attributable fraction was calculated to estimate percentages of these six outcomes that could have been prevented by supplying EBF. Results Fifty-six percent of infants were exclusively breastfed during the first 6 months. Lack of EBF increased the odds of diarrhea, fever and ARI. Among the babies aged 6 months or less 27.37% of diarrhea, 13.24% of fever and 8.94% of ARI could have been prevented if EBF was not discontinued. If EBF was terminated during 0-2 months, 2-4 months the odds of becoming underweight were 2.16 and 2.01 times higher, respectively, than babies for whom EBF was not terminated. Conclusion Children who are not offered EBF up to 6 months of their birth may suffer from a range of infectious diseases and under-nutrition. Health promotion and other public health interventions should be enhanced to encourage EBF at least up to six-month of birth. Trail registration Data of this study were collected following the guidelines of ICF International and Bangladesh Medical Research Council. The registration number of data collection is 132,989.0.000 and the data-request was registered on September 11, 2016.